Clinical outcomes in adult patients with aplastic anemia: A single institution experience. Issue 12 (25th September 2017) - Boddu, Prajwal; Garcia‐Manero, Guillermo; Ravandi, Farhad; Borthakur, Gautam; Jabbour, Elias; DiNardo, Courtney; Jain, Nitin; Daver, Naval; Pemmaraju, Naveen; Anderlini, Paolo; Parmar, Simrit; KC, Devendra; et al.
Abstract: Newer treatment modalities are being investigated to improve upon historical outcomes with standard immunosuppressive therapy (IST) in aplastic anemia (AA). We analyzed outcomes of adult patients with AA treated with various combinatorial anti‐thymoglobulin‐based IST regimens in frontline and relapsed/refractory (R/R) settings. Pretreatment and on‐treatment clinical characteristics were analyzed for relationships to response and outcome. Among 126 patients reviewed, 95 were treatment‐naïve (TN) and 63, R/R (including 32 from the TN cohort); median ages were 49 and 50 years, respectively. Overall survival (OS) was superior in IST responders ( P < .001). Partial response to IST was associated with shorter relapse‐free survival (RFS), as compared with complete response ( P = .03). By multivariate analysis, baseline platelet and lymphocyte count predicted for IST response at 3 and 6 months, respectively. While additional growth factor interventions led to faster count recovery, there were no statistically significant differences in RFS or OS across the various frontline IST regimens (i.e., with/without G‐CSF or eltrombopag). While marrow cellularity did not correlate with peripheral‐blood counts at 3 months, cytomorphological assessment revealed dyspoietic changes in all nonresponders with hypercellular‐marrow indices. Covert dysplasia, identified through early bone marrow assessment, has implications on future therapy choices after IST failure. Salvage IST response depended upon prior response to ATG: prior responders (46%) vs. primary refractory (0%) ( P < .01). In the R/R setting, there was no survival difference between IST and allogeneic stem cell transplant groups, with a trend toward superior OS in the former. Transplant benefits in the R/R setting may be underrealized due to transplant‐related mortality.